Relapsing Campylobacter jejuni Systemic Infections in a Child with X-Linked Agammaglobulinemia - Paola Ariganello; Giulia Angelino; Alessia Scarselli; Irene Salfa; Martina Della Corte; Arianna De Matteis; Patrizia D'Argenio; Susanna Livadiotti; Emma C. Manno; Cristina Russo; Andrea Finocchi; Caterina Cancrini (Case Reports in Pediatrics)
X-linked agammaglobulinemia (XLA) is a primary immunodeficiency of the humoral compartment, due to a mutation in the Bruton tyrosine kinase (BTK) gene, characterized by a severe defect of circulating B cells and serum immunoglobulins. Recurrent infections are the main clinical manifestations; although they are especially due to encapsulated bacteria, a specific association with Campylobacter species has been reported. Here, we report the case of a boy with XLA who presented with relapsing Campylobacter jejuni systemic infections. His clinical history supports the hypothesis of the persistence of C. jejuni in his intestinal tract. Indeed, as previously reported, XLA patients may become chronic intestinal carriers of Campylobacter, even in absence of symptoms, with an increased risk of relapsing bacteraemia. The humoral defect is considered to be crucial for this phenomenon, as well as the difficulties to eradicate the pathogen with an appropriate antibiotic therapy; drug resistance is raising in Campylobacter species, and the appropriate duration of treatment has not been established. C. jejuni should always be suspected in XLA patients with signs and symptoms of systemic infection, and treatment should be based on antibiogram to assure the eradication of the pathogen.